Discovery of multifold modified sialosides as human CD22/siglec-2 ligands with nanomolar activity on B-cells - Prescher, Horst; Brossmer, Reinhard (ACS chemical biology, 2014)
Sialic acids are abundant in higher domains of life and lectins recognizing sialosaccharides are heavily involved in the regulation of the human immune system. Modified sialosides are useful tools to explore the functions of those lectins, especially members of the Siglec (sialic acid binding immunoglobulin like lectin) family. Here we report design, synthesis, and affinity evaluation of novel sialoside classes with combined modification at positions 2, 4, and 9 or 2, 3, 4, and 9 of the sialic acid scaffold as human CD22 (human Siglec-2) ligands. They display up to 7.5 × 105-fold increased affinity over αMe Neu5Ac (the minimal Siglec ligand). CD22 is a negative regulating coreceptor of the B-cell receptor (BCR). In vitro experiments with a human B-lymphocyte cell line showed functional blocking of CD22 upon B-cell receptor (BCR) stimulation in the presence of nanomolar concentrations of the novel ligands. The observed increased Ca2+ response corresponds to enhanced cell activation, providing an opportunity to therapeutically modulate B-lymphocyte responses, e.g., in immune deficiencies and infections.